Hyperbaric oxygen therapy for carbon monoxide poisoning: a survey of emergency medical centers in Japan - Ogawa, Yoshihito; Nokubi, Motonari; Yazawa, Kazuyuki; Umemura, Yutaka; Sueyoshi, Koichiro; Takehara, Nobuharu; Takimoto, Hiroki (Nihon Kyukyu Igakukai Zasshi, 2012)
Acute carbon monoxide (CO) poisoning is common, but the role of hyperbaric oxygen (HBO) therapy remains controversial. To evaluate the current situation regarding CO poisoning and HBO therapy, we sent a questionnaire to all 218 emergency medical centers in our country asking the approximate number of patients treated per year for CO poisoning, whether the center had an HBO chamber, protocols for HBO therapy, and details of patients with persistent neurological sequelae. We received 108 valid responses (50%), including 45 (42%) from centers who treated 5-10 cases per year and 38 (35%) from centers who treated <5 cases per year. Forty-five centers (42%) had an HBO chamber, of which 40 used their chambers to treat CO poisoning. Twelve centers used HBO therapy for all cases of CO poisoning, and 12 used HBO therapy only for cases with delayed neuropsychological sequelae. HBO therapy protocols were highly variable. Twelve patients with delayed neuropsychological sequelae were reported, all of which developed within 30 days. HBO therapy was performed in 8 of these 12 cases, with a range of 1 to 80 sessions. HBO therapy for CO poisoning remains controversial and differs depending on the treatment center and the attending physician. It is necessary for our country to establish guidelines for HBO therapy through rigorous clinical trials.